2005
DOI: 10.1016/j.jcf.2005.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and family functioning and quality of life in adolescents with cystic fibrosis

Abstract: Adolescents with CF appear to be a psychologically well functioning and well-adjusted group. These findings support the importance of a more sophisticated model of well-being for adolescents with CF, which explores the young person's views on their quality of life and wider support frameworks rather than relying solely on measures of physical health to gauge well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 32 publications
(27 reference statements)
6
67
0
2
Order By: Relevance
“…This analysis included FEV 1 and FEV 1 /FVC data collected closest to the dates of completed HRQOL measures. We used data representing patients' baseline pulmonary has been measured in short-term CF-related intervention studies [5][6][7][8][9] and cross-sectional psychosocial research, [10][11][12][13] the relationship between NBS and HRQOL in children and adolescents has not been thoroughly evaluated. Thus far, the RCT has consistently revealed better nutritional status among presymptomatic patients with CF diagnosed through NBS (early diagnosis group) compared with those with CF diagnosed traditionally by symptom identifi cation (control group).…”
Section: Methodsmentioning
confidence: 99%
“…This analysis included FEV 1 and FEV 1 /FVC data collected closest to the dates of completed HRQOL measures. We used data representing patients' baseline pulmonary has been measured in short-term CF-related intervention studies [5][6][7][8][9] and cross-sectional psychosocial research, [10][11][12][13] the relationship between NBS and HRQOL in children and adolescents has not been thoroughly evaluated. Thus far, the RCT has consistently revealed better nutritional status among presymptomatic patients with CF diagnosed through NBS (early diagnosis group) compared with those with CF diagnosed traditionally by symptom identifi cation (control group).…”
Section: Methodsmentioning
confidence: 99%
“…Limited daily functioning, poor adherence to treatment, low self-esteem, short stature, and impaired psychosocial outcomes have been reported. [10][11][12][13][14][15] What remains less well known is how young patients cope with the symptoms, prognostic uncertainty, and treatment burden of CF. In-depth insights into people' s beliefs and attitudes can be gained by qualitative research, and synthesis of multiple qualitative studies can provide a broader scope of data across different health care contexts and generate new and more comprehensive understandings of social phenomena.…”
mentioning
confidence: 99%
“…Several studies have described psychological problems in patients with CF21 but only three, to our knowledge, have explored the relationship with HRQoL (4,5,22). Szyndler et al (22) found that Australian adolescents with CF exhibited psychopathology levels lower than their non-diseased peers (12.5%); however, increased psychopathology was associated with lower ratings on several quality of life scores.…”
Section: Discussionmentioning
confidence: 99%
“…Szyndler et al (22) found that Australian adolescents with CF exhibited psychopathology levels lower than their non-diseased peers (12.5%); however, increased psychopathology was associated with lower ratings on several quality of life scores. Riekert et al (4) found a 30% prevalence of depressive symptoms among adult patients, a figure similar to ours; in all HRQoL domains, patients with both depressive symptoms and poor lung function reported significantly worse scores than those without depressive symptoms, regardless of lung function status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation